Disrupsi Kecerdasan Buatan dan Reduksi Peran Manusia dalam Dunia Kerja - Eko Susanto; M. Abzar D.; Abdul Majid (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Technological advances, especially artificial intelligence (AI), have had a significant impact on the world of work. Various jobs that were previously done by humans are now being replaced by automated systems and AI-based robots. This phenomenon has consequences for human resources, both in terms of efficiency and job loss. This article aims to analyze the impact of AI on human employment opportunities and examine the readiness of the workforce to face the digital era. This study uses a literature study method with a descriptive-analytical approach. The results of the study show that although AI provides advantages in time and cost efficiency, it also poses a challenge for the workforce who are not ready to adapt to these changes. Therefore, a strategy to improve workforce skills is needed to remain relevant in digital-based industries.